Areas of Smart Specialisation and the Romanian Research - DRĂGOIU, Codruța Ilinca (Journal of Economic Development, Environment and People, 2017)
This article aims at identifying the areas of smart specialisation presence in the Romanian research and strategies in the field. A succinct picture of national goals and the evolution of the areas of smart specialisation in Romanian research have been outlined by reviewing research policies at EU and Romanian level.